2004
DOI: 10.1074/jbc.m407681200
|View full text |Cite
|
Sign up to set email alerts
|

Desulfoglucosinolate Sulfotransferases from Arabidopsis thaliana Catalyze the Final Step in the Biosynthesis of the Glucosinolate Core Structure

Abstract: The phytotoxin coronatine is a structural analog of octadecanoid signaling molecules, which are well known mediators of plant defense reactions. To isolate novel coronatine-regulated genes from Arabidopsis thaliana, differential mRNA display was performed. Transcript levels of CORI-7 (coronatine induced-7) were rapidly and transiently increased in coronatine-treated plants, and the corresponding cDNA was found to encode the sulfotransferase AtST5a. Likewise, upon wounding, an immediate and transient increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 46 publications
7
155
0
Order By: Relevance
“…To date, some of these candidate genes have been characterized experimentally. The predicted functions of the AtSOTs and UGT74B1 have been confirmed by concurrent studies Piotrowski et al 2004;Douglas Grubb et al 2004).…”
Section: Prediction Of the Genes Involved In Glucosinolate Biosynthessupporting
confidence: 53%
See 1 more Smart Citation
“…To date, some of these candidate genes have been characterized experimentally. The predicted functions of the AtSOTs and UGT74B1 have been confirmed by concurrent studies Piotrowski et al 2004;Douglas Grubb et al 2004).…”
Section: Prediction Of the Genes Involved In Glucosinolate Biosynthessupporting
confidence: 53%
“…SUR1 and UGT74B1, the genes involved in both Met-and Trp-derived GSL biosynthesis (Mikkelsen et al 2004;Douglas Grubb et al 2004), are in the boundary region of two modules. It has been reported that the preferable substrates of the AtSOT17 product are Met-and Phe-derived GSLs (Klein et al 2006;Piotrowski et al 2004). Although graph structure depends on the dataset and the measure of similarity used, it may possibly suggest the functional relationship of the genes.…”
Section: Prediction Of the Genes Involved In Glucosinolate Biosynthesmentioning
confidence: 99%
“…These results confirmed that the three sulfotransferase-like genes, which clustered with known GLS biosynthesis genes after BL-SOM analysis, actually encode the proteins catalyzing PAPS-dependent sulfation of desulfo-GLSs to GLSs. During the reviewing process of this publication, Piotrowski et al (23) reached the same conclusion by quite different strategy to ours and reported that these three genes encode desulfo-GLS sulfotransferase. It was also the case with At1g24100, which was assumed to encode S-glucosyltransferase involved in GLS biosynthesis (24).…”
Section: Resultsmentioning
confidence: 50%
“…A second oxidation step leads to an aci-nitro compound, catalyzed by CYP83A1 (Hemm et al, 2003;Naur et al, 2003), which is then conjugated with a sulfur donor into S-alkyl thiohydroximate. The final biosynthetic steps comprise consecutive actions catalyzed by C-S lyases , UDP-glucosyltransferases (Grubb et al, 2004), and sulfotransferases (ST5b and ST5c; Piotrowski et al, 2004). Recently, the R2R3-MYB transcription factors HAG1/MYB28, HAG2/MYB76, and HAG3/MYB29 were identified as regulators of Met-derived glucosinolate biosynthesis, with High Aliphatic Glucosinolate 1 (HAG1/MYB28) being the main player (Gigolashvili et al, 2007(Gigolashvili et al, , 2008Hirai et al, 2007;Sønderby et al, 2007).…”
Section: Introductionmentioning
confidence: 99%